2000
DOI: 10.1038/sj.emboj.7592140b
|View full text |Cite
|
Sign up to set email alerts
|

Cellular transcription factors recruit viral replication proteins to activate the Epstein–Barr virus origin of lytic DNA replication, oriLyt

Abstract: (1997) Cloning and characterization of a transcription factor that binds to the proximal promoters of the two mouse type I collagen genes. J. Biol. Chem., 272, 4915-4923. Passantino,R., Antona,V., Barbieri,G., Rubino,P., Melchionna,R., Cossu,G., Feo,S. and Giallongo,A. (1998) Negative regulation of beta enolase gene transcription in embryonic muscle is dependent upon a zinc finger factor that binds to the G-rich box within the musclespecific enhancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…BZLF1 has been reported to interact with the viral helicase -primase complex (Table 1) (Liao et al 2001(Liao et al , 2005El-Guindy et al 2010) and the viral polymerase accessory factor BMRF1 (Takagi et al 1991;Daikoku et al 2005;Nakayama et al 2009). BMRF1 bears structural similarities with cellular PCNA Nakayama et al 2010) and could potentially provide an additional tethering function for the replication complex (Zhang et al 1997;Baumann et al 1999). In addition, the primase-associated factor might serve a similar tethering function in conjunction with cellular, oriLyt-binding proteins (see below and Liao et al 2005).…”
Section: Proteins That Support the Functions Of Orilytmentioning
confidence: 99%
See 1 more Smart Citation
“…BZLF1 has been reported to interact with the viral helicase -primase complex (Table 1) (Liao et al 2001(Liao et al , 2005El-Guindy et al 2010) and the viral polymerase accessory factor BMRF1 (Takagi et al 1991;Daikoku et al 2005;Nakayama et al 2009). BMRF1 bears structural similarities with cellular PCNA Nakayama et al 2010) and could potentially provide an additional tethering function for the replication complex (Zhang et al 1997;Baumann et al 1999). In addition, the primase-associated factor might serve a similar tethering function in conjunction with cellular, oriLyt-binding proteins (see below and Liao et al 2005).…”
Section: Proteins That Support the Functions Of Orilytmentioning
confidence: 99%
“…TD was found to be the binding site for several cellular proteins (Gruffat et al 1995). The transcription factors Sp1, Sp3, and ZBP-89, have been identified and shown to make essential and direct contributions to oriLyt's function(s) (Gruffat et al 1995;Baumann et al 1999). They interact with EBV's DNA polymerase and its processivity factor and likely tether viral replication proteins to oriLyt via direct protein -protein interactions at (Liao et al 2005) within the previously identified oriLyt enhancer region (Yates 1996) and colocalize EBV's helicase -primase complex to operationally defined replication compartments in lytically induced cells.…”
Section: Proteins That Support the Functions Of Orilytmentioning
confidence: 99%
“…26 By recruiting the viral replication proteins or forming a viral initiation complex, it plays an important regulatory role in the virus DNA replication. 27,[49][50][51] In addition, several cellular factors, including C/EBP, p53, NFκB, c-Myb and CBP have been proposed to be involved in the regulation of Zta activities. However, the detailed mechanisms of lytic cycle DNA replication of EBV are still poorly understood.…”
Section: Characterization Of Ztamentioning
confidence: 99%
“…The activation of EBV in latently infected memory B-cells is in response to the cellular transcription factors 50 or the signals for driving B-cells to differentiate into plasma cells or by cross-linking the surface immunoglobulin with an anti-Ig antibody. 104,105 EBV IE genes are induced directly by signal transduction from B-cell receptor.…”
Section: Zta As a Target Of Anticancer Therapymentioning
confidence: 99%
“…The six core replication factors encoded by EBV are the DNA polymerase (BALF5); the polymerase processivity factor (BMRF1); the helicase (BBLF4); the primase (BSLF1); the primase associated factor (BBLF2/3), and the single-stranded DNA binding protein (BALF2) (El-Guindy, Heston & Miller 2010). The function of tethering replication proteins to oriLyt is not limited to ZEBRA; the transactivation domains of Sp1 and ZBP89 interact with BMRF1 and BALF5 and target them to the downstream region of oriLyt (Baumann et al 1999). Similarly, ZBRK1, a cellular DNA binding zinc finger protein, serves as a contact point for BBLF2/3 on oriLyt (Liao et al 2005).…”
Section: Role Of Zebra During Viral Replicationmentioning
confidence: 99%